The handbook of microbial bioresources - Gupta, Vijai Kumar; Sharma, G. D. (Gauri D.); Tuohy, Maria G.; Gaur, Rajeeva (CABI, 2016)
This book, inclusive of 39 chapters, provides a detailed discussion on the biotechnological methods and processes, as well as the industrial applications, of various microbial resources. Current use of these microbial resources in the medical (anti-cancer substances from bacteria), agricultural (i.e., mycorrhizal fungi, biofertilizers, insect pest control), food (i.e., probiotics, prebiotics), feed, cosmetic, biofuel, and bioremediation industries are highlighted, giving researchers in these various fields a valuable resource for the latest developments in microbial bioresources.